2018
DOI: 10.12659/pjr.900634
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Septal Deviation and Concha Bullosa – Do They Have an Impact on Maxillary Sinus Volumes and Prevalence of Maxillary Sinusitis?

Abstract: SummaryBackgroundThe aim of the study was to assess if the presence of nasal septal deviation and concha bullosa is connected with the development of sinuses and the incidence of inflammation within them.Material/MethodsWe retrospectively analysed 214 patients who underwent paranasal sinus computed tomography. There were 125 females and 89 males, the mean age being 47.67±16.74 years (range 18–97). Exclusion criteria included: age under 18 years, prior sinonasal surgery and S-shaped septum.ResultsMean volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
43
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 46 publications
10
43
0
6
Order By: Relevance
“…The present study showed the presence of septum deviation in 24.6% of cases; in the literature, frequencies of septum deviation varying from 9% to 80% have been presented, depending on the population and methodology 4,5,13,14,[16][17][18][19] . Some authors mention septum deviation as the most common anatomical alteration in the nasal cavity 18 .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The present study showed the presence of septum deviation in 24.6% of cases; in the literature, frequencies of septum deviation varying from 9% to 80% have been presented, depending on the population and methodology 4,5,13,14,[16][17][18][19] . Some authors mention septum deviation as the most common anatomical alteration in the nasal cavity 18 .…”
Section: Discussionmentioning
confidence: 53%
“…Despite this wide range, most studies report a high frequency of NSD, so we suggest that such differences can be explained due to the methodology used. Most studies analyses image data from CT images of patients presenting clinical problems related to the nasal cavity 5,8,10,13,14 . The literature also reports a robust association between nasal concha hypertrophy and the side to which the nasal septum is diverted 1,4,11,13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The prevalence of concha bullosa is about 35%. 11,12 Although most ENT surgeons perform an outpatient endoscopy of the nose to look for synchronous pathology, the most common obstructive pathology which could be missed is the concha bullosa. This is best identified on a computed tomography scan of paranasal sinuses and is hence a radiological diagnosis.…”
Section: Synopsis Of Key Findingsmentioning
confidence: 99%